Vulvovaginal candidiasis (VVC): A review of the literature - Ni Nyoman Lidya Trisnadewi (Explorer Front, 2020)
Vulvovaginal candidiasis (VVC) is the second most common cause of vaginitis after bacterial vaginosis. VVC often occurs in women of reproductive age (20-40 years). Risk factors for VVC can be divided into two, such as host factors (pregnancy, hor-mone replacement, uncontrolled diabetes mellitus, immunosuppression, antibiotics, use of glucocorticoids, genetic influences) and behavioral factors (oral contracep-tives, sexual habits, hygiene, and clothes that are used). To diagnose VVC in a per-son, evaluation from anamnesis and clinical manifestation can be conducted. It can also be confirmed by laboratory examination. The management is based on the clas-sification. Uncomplicated VVC is most effectively treated with topical azoles, but a single dose of fluconazole can also be given orally. Treatment of VVC with compli-cations can be given fluconazole 150 mg for 3 days or topical azole for 7 days. However, when the VVC case that caused by non-albicans Candida not responding to conventional treatment such as antimycotics, the amphotericin B can be given to cure the disease. VVC caused by Candida glabrata can be given topical boric acid or flucytosine. This article consists of several theoretical references that have been viewed to have a better understanding of candidiasis vulvovaginitis.